Haihun Marquis Tomb in Western Han Dynasty: Social Value and Future Prospects - A Knowledge Graph Analysis with Citespace - Dai, Yijun; Sangiamvibool, Arkom (Journal of Ecohumanism, 2024)
This paper uses the CiteSpace knowledge graph visualization tool to analyze the research evolution path and trend of 583 academic papers in the CNKI database in the past ten years. The results show that the unique position of the tomb of the Haihun Marquis in the field of history and cultural heritage of the Han Dynasty, the mainstream of research in the field of Han Dynasty culture, artistic innovation and application, the evolution of cultural heritage research, and the interdisciplinary research of the deep integration of cultural heritage research and advanced technology in the future will provide strong support for promoting the cultural and museum industry and the recreation of traditional Chinese culture.